2020
DOI: 10.3390/cancers12040919
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate Affects T Antigen Expression and Survival of Virus-Positive Merkel Cell Carcinoma

Abstract: Merkel cell carcinoma (MCC) is a rare and highly aggressive skin cancer with frequent viral etiology. Indeed, in about 80% of cases, there is an association with Merkel cell polyomavirus (MCPyV); the expression of viral T antigens is crucial for growth of virus-positive tumor cells. Since artesunate-a drug used to treat malaria-has been reported to possess additional anti-tumor as well as anti-viral activity, we sought to evaluate pre-clinically the effect of artesunate on MCC. We found that artesunate repress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…However, some molecules not specific for MCPyV show anti-viral activity in cell culture and xenograft models. The malaria drug artesunate reduces growth and survival of VP-MCC cells in vitro and VP-MCC tumors in a xenograft mouse model, but had no or little effect on primary fibroblasts, melanoma cell lines, and non-classical VN-MCC cell lines [ 259 ]. Artesunate down-regulated expression of LT, but only in one VP-MCC cell line was the sensitivity towards artesunate reduced upon knockdown of LT expression.…”
Section: Vp-mcc Specific Therapymentioning
confidence: 99%
“…However, some molecules not specific for MCPyV show anti-viral activity in cell culture and xenograft models. The malaria drug artesunate reduces growth and survival of VP-MCC cells in vitro and VP-MCC tumors in a xenograft mouse model, but had no or little effect on primary fibroblasts, melanoma cell lines, and non-classical VN-MCC cell lines [ 259 ]. Artesunate down-regulated expression of LT, but only in one VP-MCC cell line was the sensitivity towards artesunate reduced upon knockdown of LT expression.…”
Section: Vp-mcc Specific Therapymentioning
confidence: 99%
“…ART Chauhan et al (138) found that ART induced ROS production and subsequent cell death in a receptor-interacting protein 1-dependent manner in human renal carcinoma. ART exerted a potent antiproliferative effect on polyomavirus-positive Merkel cell carcinoma (MCC) cells with good overall tolerance and induced ferroptosis (139). In addition, ART also significantly suppressed the growth of established MCC tumors in xenotransplanted mice, suggesting that ART may be used for the treatment of MCC (138).…”
Section: Potential Role Of Art In Human Malignanciesmentioning
confidence: 99%
“…Artemisinin, extracted from Artemisia annua (Sweet Wormwood), was developed in Traditional Chinese Medicine to treat malaria (14). Artesunate (ART) (Figure 1A), derived from artemisinin, exhibits remarkable anti-cancer activity towards a broad variety of tumor cell lines (15,16), including prostate carcinoma (17)(18)(19). Moreover, ART exhibits antiinflammatory properties, thereby preventing tissue destruction induced by carcinogens in vivo (20).…”
Section: Introductionmentioning
confidence: 99%